Limocitrin induced cellular death through ERK pathways in human oral squamous cell cancer - Bharath Kumar Velmurugan; Chia-Chieh Lin; Min-Yun Kao; Hsin-Yu Ho; Yu-Sheng Lo; Yi-Ching Chuang; Ming-Ju Hsieh (Scientific Reports)
Abstract This study sought to investigate the anticancer efficacy of limocitrin on two distinct human oral cancer cell lines. At first, we evaluated the effect of limocitrin on the proliferation of OSCC cells (SCC-9 and SCC-47) using MTT and colony formation assays. Limocitrin treatment increased cell cycle arrest at G2/M phase, induced caspase-related apoptosis (cleaved caspase-3, caspase-8, caspase-9 and PARP expression) in OSCC cells. Limocitrin treatment inhibited Bcl-2 and Bcl-XL and induced Bax, Bak expression in both SCC-9 and SCC-47 cell lines. Limocitrin treatment inhibited cyclin E1, E2, CDK2, CDK4, and CDK6 and increased p21 expression. Limocitrin also exhibited an inhibitory effect on the phosphorylation of AKT, ERK1/2 and JNK in a dose-dependent manner. Additionally, pretreatment of oral cancer cells with U0126 resulted in increased cleaved caspase-3 and caspase-8 and PARP expression. Furthermore, limocitrin treatment decreased XIAP, cIAP1, HSP27 protein expression than control group. Combined treatment with limocitrin and si-XIAP significantly increased cleaved PARP, caspase-3 and -8 expressions in SCC-9 cells. Overall, this evidence indicates that limocitrin may serve as an effective anticancer agent for the treatment of oral cancer.